Improving Student’s Curiosity by ICT-Assisted Guided Inquiry Models - Irdalisa Irdalisa; Mega Elvianasti; Maesaroh Maesaroh; Husnin Nahry Yarza; Tuti Marjan Fuadi (STAI Hubbulwathan Duri, 2021)
The purpose of this research is that students' curiosity can be increased by using guided inquiry models assisted by ICT. In learning science, one of the things that must be improved is curiosity. Curiosity is a person's desire for information and knowledge, as well as the sensation of new experiences to be able to motivate behavior in finding out the true truth. The curiosity measured in this study, such as the desire of students to explore for new information, the desire to find a new concept or theory by applying the knowledge they have, and someone's desire to find out if there is a conflict between what is believe inversely proportional with what is reality. This study used a one group pretest posttest design and used a quantitative approach. The sample in this study was 63 fifth semester students of biology education at the University of Muhammadiyah Prof. Dr. Hamka Jakarta, Indonesia. The sample was taken by using purposive sampling technique. The research instrument used a questionnaire. Data analysis using descriptive quantitative. Based on the research results, it can be concluded that the application of the ICT-assisted guided inquiry model is more effective in increasing student curiosity. The application of technology-based inquiry is important in improving student Curiosity to make science learning more meaningful, effective, and efficient.